Analisis Kerusakan Jalan dan Penanganan Pada Ruas Jalan Sullukan – Tandung Kabupaten Toraja Utara - Valentino Tandiongan; Benyamin Tanan; Monalisa Bumbungan (Paulus Civil Engineering Journal, 2023)
This research was conducted on the Sullukan – Tandung road North Toraja Utara Regency with a total length of 1 km with a road witdh of 3 m, the road section is divide into 10 segments. The aim of the research is to identify and analyze the level of damage and how to handle it. This research method is to carry out measurements for each type of damage, and calculate the volume of vehicle traffic. How to analyze the level of damage using the PCI method and handling damage refers to the method of highways. The results of this study using the PCI method amounted to 58.4% in the good category (Good). Handling types of damage to the Sullukan – Tandung road section North Toraja Regency such as : Laburan asphalt (BURAS), Thin layer of sand asphalt (LATASIR), One layer asphalt layer (BURTU), Two layer stone laburan (BURDA), and repair of thick layers of road pavement on severely damaged segments.